2020
DOI: 10.1002/jbt.22515
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of heat shock protein 70 enhanced mesenchymal stem cell treatment efficacy in phosgene‐induced acute lung injury

Abstract: In our previous study, we have confirmed that in phosgene‐induced acute lung injury (ALI) rats, mesenchymal stem cells (MSCs) can treat the disease. Moreover, heat shock protein 70 (Hsp70) can be used as a protective protein, and Hsp70 upregulated drastically when exposed to stressful conditions. We aimed to assess that MSCs overexpressed Hsp70 could enhance the capacity of MSCs and have a good therapeutic effect on phosgene‐induced ALI. We transduced MSCs with Hsp70 and then we tested the function of the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…[26] Furthermore, MSCs pretreated via different methods could have a better therapeutic effect on phosgene-induced ALI than nonpretreated MSCs. [27,28] The exosome is an essential microenvironment that affects cell function. [29] For instance, exosomes released by breast cancer cells could transform MSCs into tumor-forming cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] Furthermore, MSCs pretreated via different methods could have a better therapeutic effect on phosgene-induced ALI than nonpretreated MSCs. [27,28] The exosome is an essential microenvironment that affects cell function. [29] For instance, exosomes released by breast cancer cells could transform MSCs into tumor-forming cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Furthermore, MSCs pretreated via different methods could have a better therapeutic effect on phosgene‐induced ALI than nonpretreated MSCs. [ 27,28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have confirmed the related mechanisms of action from various aspects, including regulation of the proliferation and differentiation of lung epithelial cells and endogenous lung stem cells ( 56 ) and repair via the proliferation of endogenous lung stem cells ( 94 ). Although most studies focusing on experimental models have demonstrated their validity, MSCs provide strong prospects for treating P-ALI ( 6 , 52 , 53 , 94 98 ) ( Table 2 ). MSC-based therapy has been widely used in the clinical treatment stage of ARDS and has also achieved very good effects, and it is expected to be studied in the P-ALI clinic in the near future.…”
Section: Treatmentmentioning
confidence: 99%
“…Modifying MSCs to enhance their homing and migration abilities has achieved initial success in a P-ALI animal model. Jin et al used MSCs overexpressing heat shock protein 70 (Hsp70) to treat P-ALI and surprisingly found that Hsp70 activated the PI3K/AKT pathway to promote MSC survival and migration [96]. In addition, by upregulating the level of the SDF1-specific receptor CXCR7, the ability of MSCs to directionally migrate and differentiate into ATII could be enhanced [97,98].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%